2003
DOI: 10.3354/meps246225
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and population structure of the Atlantic horseshoe crab Limulus polyphemus in Pleasant Bay, Cape Cod

Abstract: Populations of horseshoe crabs Limulus polyphemus are widely distributed from Maine to the Gulf of Mexico, are commercially harvested, and are thought to have decreased in abundance in recent decades. To provide information needed to manage exploited populations of horseshoe crabs, we conducted comprehensive field sampling in a major shallow estuary containing preferred habitat for horseshoe crabs. The data we obtained are the first to comprehensively define abundance, determine sex ratios of horseshoe crabs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 37 publications
8
57
2
1
Order By: Relevance
“…The condition of the individual, which is probably age related, is also a factor in stranding-related mortality (Penn and Brockmann 1995;Smith et al 2010). Carmichael et al (2003) found that in Pleasant Bay, Massachusetts, adults had a lower estimated mortality rate than juveniles, and there was no significant difference in estimated mortality rate for adult males and females. In contrast, Butler (2012) found through analysis of mark-recapture data from Delaware Bay that adult male annual survival (77%, SE = 0.04) was greater than adult female survival (65%, SE = 0.09).…”
Section: Mortalitymentioning
confidence: 98%
See 3 more Smart Citations
“…The condition of the individual, which is probably age related, is also a factor in stranding-related mortality (Penn and Brockmann 1995;Smith et al 2010). Carmichael et al (2003) found that in Pleasant Bay, Massachusetts, adults had a lower estimated mortality rate than juveniles, and there was no significant difference in estimated mortality rate for adult males and females. In contrast, Butler (2012) found through analysis of mark-recapture data from Delaware Bay that adult male annual survival (77%, SE = 0.04) was greater than adult female survival (65%, SE = 0.09).…”
Section: Mortalitymentioning
confidence: 98%
“…Growth is relatively rapid during the first several years, progressing through stages I-V in the first year, stages VI-VII the second year, stages VII-IX the third year, with a single molt per year after that until reaching maturity (Shuster 1982). The pattern of development appears to the same throughout the species' range despite large regional differences in environmental attributes (Estes et al 2015;Carmichael et al 2003). Shuster (1950) approximated that it took 9-12 years for horseshoe crabs to reach sexual maturity.…”
Section: Development and Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…With a characteristically high mortality rate the early stages of life for numerous marine species, approximately 0.001% of crabs survive through the first year (Carmichael et al, 2003;Sweka et al, 2007). Researchers have had some success from collecting horseshoe crab eggs, rearing them in a laboratory, and releasing the crabs as juveniles.…”
Section: Alternatives To Current Horseshoe Crab Harvesting Practicesmentioning
confidence: 99%